Low-temperature tribological properties of Si3N4 ceramic composites incorporating nano/microscale graphene and Si3N4 whisker - Fei Chen; Xiaobo Sun; Bin Fang; Ke Yan; Bei Yan (Journal of Materials Research and Technology)
Si3N4 ceramic bearings have demonstrated significant potential in augmenting the performance of liquid rockets. However, the operational conditions, including reciprocating use, ultra-high-speeds, and high-load impacts, impose more stringent requirements on their self-lubricating performance. Consequently, the cryogenic tribological properties of Si3N4 ceramic composites with hybrid of multilayer graphene (MLG) and β-Si3N4 whisker (β-Si3N4w) were thoroughly investigated in this work. The enhanced interatomic binding energy and friction-induced thermal diffusion were identified as contributing factors to the improved low-temperature tribological properties of Si3N4 ceramic composites. At a temperature of 77 K, the friction coefficient of Si3N4 ceramic composites containing 1 wt% MLG and 3 wt% β-Si3N4w, synthesized via spark plasma sintering, dropped to 0.16–0.20, representing a decrease of 39.39–44.83% compared to that at ambient temperature. Microscopic analysis of the worn surfaces indicated that adhesive wear was the predominant wear form for Si3N4 ceramic composites under low-temperature conditions. The above research is anticipated to furnish essential insights for the cryogenic self-lubricating design of ceramic composites.